The gold eaters - Wright, Ronald, 1948- (Riverhead Books, 2015)
"Plucked from his small fishing village and captured by the conquistadors looking to plunder the gold of Peru, young Waman is the everyman thrown into extraordinary circumstances, caught up in history's throes. He finds himself at every major moment in the empire-building of the Spanish explorers, including Francisco Pizarro, and in the culture clash and violent overthrow of the Incan leaders. He becomes an indispensable translator between the two worlds, who must learn political gamesmanship in order to survive and so that he can one day find the love of his life and be reunited with his family. Based closely on real historical events, The Gold Eaters draws on Ronald Wright's expert knowledge of sixteenth-century South America, as well as his imaginative ability to bring to life an unforgettable epoch and a world forged anew from violence and upheaval"--